A thick coating suitable for silicon steel surface and preparation method thereof
Through the synergy between the modified graphene-silver nanoparticle composite and a variety of functional components, a silicon steel surface coating with excellent comprehensive performance was prepared, which solved the problems of insufficient adhesion, heat resistance and corrosion resistance of existing coatings, and significantly improved the performance and service life of the coating.
Patent Information
- Application Number
- CN202411634479.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The existing silicon steel surface coatings have problems such as insufficient adhesion, insufficient heat and corrosion resistance, complex preparation process and high cost, and it is difficult to meet the performance requirements under extreme operating conditions.
The coating is prepared by mixing modified graphene-silver nanoparticle composite, hydrogen-containing silicone oil, additive solution and ultraviolet absorber, and uniformly coated by spraying method and high-temperature curing treatment to ensure the complete curing and long-term stability of the coating.
It improves the conductive, antibacterial properties, hardness, wear resistance, ultraviolet and chemical corrosion resistance of the coating, extends the service life of the coating, and solves the problems of poor dispersion and unstable performance of traditional coatings.
Smart Images

Figure CN119119868B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal coating preparation, and relates to a metal coating, in particular to a thick coating suitable for the surface of silicon steel and a preparation method thereof. Background Art
[0002] Silicon steel, as an indispensable key material in the power industry, is widely used in the manufacture of electromagnetic equipment such as motors and transformers. Its excellent electromagnetic properties make silicon steel play a vital role in the conversion and transmission of electric energy. However, in actual application, the surface of silicon steel is easily eroded by various environmental factors, such as oxidation and corrosion, which not only affects the performance of silicon steel, but also shortens its service life.
[0003] In order to meet these challenges, researchers are constantly exploring and improving the protective technology for the surface of silicon steel. Although existing coatings have improved the protective performance of silicon steel to a certain extent, there are still many disadvantages. First, the adhesion problem of coatings is still prominent. Many coatings will fall off after long-term use, resulting in a significant reduction in the protective effect. Secondly, the heat resistance and corrosion resistance of coatings also need to be improved, especially in extreme working conditions, such as high temperature and high humidity environments, the performance of coatings often cannot meet the needs.
[0004] In addition, the coating preparation process is complex and costly, which is also an important problem in the current application of silicon steel surface coatings. This not only increases the production cost of enterprises, but also limits the widespread application of coatings.
[0005] In view of the above-mentioned status quo and existing problems, the present invention proposes a method for preparing a thick coating suitable for the surface of silicon steel. The present invention designs a modified graphene, and evenly mixes components such as modified graphene-silver nanoparticle composites, hydrogen-containing silicone oil, auxiliary solution and ultraviolet absorbers to prepare a coating with excellent comprehensive performance. The coating not only has excellent conductivity and antibacterial properties, but also has the characteristics of high hardness, wear resistance, UV resistance and chemical corrosion resistance. In addition, the present invention adopts a spraying method to achieve uniform coating of the coating, and ensures the complete curing and long-term stability of the coating through high-temperature curing treatment. These improvement measures not only solve the problems of poor dispersibility of traditional graphene and unstable performance of composite materials, but also significantly improve the comprehensive performance and service life of the coating. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a method for preparing a thick coating suitable for the surface of silicon steel. The present invention is implemented as follows: a thick coating suitable for the surface of silicon steel and a method for preparing the same, which specifically comprises the following steps:
[0007] S1. Weigh 5-6 g of graphene and disperse it in 80-100 mL of ethanol. Use an ultrasonic disperser to sonicate at a frequency of 40 kHz for 20-30 min to form a uniform graphene dispersion. Weigh 3-5 g of polyethylene glycol diglycidyl ether (PEGDGE) and slowly add it to the graphene dispersion while stirring and continue sonication for 50-60 min to obtain a modified graphene dispersion. Use a centrifuge to centrifuge at 2000-3000 r / min for 3-5 min to remove excess solvent and unadsorbed modifier, and then vacuum dry at 60-80 °C for 18-24 h to obtain modified graphene powder. The PEGDGE added in this step fixes PEGDGE on the graphene surface through surface adsorption and chemical bonding, and uses the steric hindrance effect of PEGDGE to improve the dispersibility and stability of graphene. The introduction of PEGDGE provides graphene with additional functional expansion capabilities.
[0008] S2, the graphene powder obtained in step S1 is redispersed in 50-60 mL ethanol, and slowly added to 30-40 mL ethanol solution in which 2-3 g silver nitrate is dissolved, stirring while adding, and setting the speed of the magnetic stirrer to 500-600 rpm to ensure uniform mixing. Weigh 0.1-0.2 g of sodium borohydride, quickly add it to the mixed solution, and immediately increase the speed of the magnetic stirrer to 800-900 rpm to ensure that the reducing agent is quickly dispersed and promotes the reduction reaction. Continue stirring for 2-2.5h to allow the reduction reaction to proceed fully. After the reaction is completed, the mixed solution is ultrasonically treated for 25-30 min to further break up the agglomerates that may be formed and improve the uniformity and dispersibility of the modified graphene-silver nanoparticle composite. The mixed solution after ultrasonic treatment is centrifuged, and the speed is set to 2000-3000 r / min for 3-5 min to remove unreacted silver nitrate, reducing agent and ethanol solvent. After centrifugation, the precipitate is washed 3-5 times with anhydrous ethanol to completely remove impurities. Finally, the washed precipitate is placed in a vacuum drying oven and dried at 50-60 ° C to constant weight to obtain a pure modified graphene-silver nanoparticle composite. The introduction of silver nanoparticles in this step significantly improves the conductivity of the composite material, which is helpful for the application of the coating in electromagnetic shielding, antistatic and other aspects. In addition, silver nanoparticles have excellent antibacterial properties and can give the coating antibacterial function.
[0009] S3, dissolve 10-12 g of vinyl triethoxysilane in 60-70 mL of acetone, marked as solution A, and dissolve 2-4 g of stannous octoate in 20-30 mL of acetone, marked as solution B. Then mix the two solutions and place them in a microwave ultrasonic device. Set the microwave power to 600-800 W, the ultrasonic frequency to 20 kHz, and the reaction time to 45-60 min to obtain a uniform and transparent additive solution. The additive solution synthesized in this step helps to promote the cross-linking reaction of the silicone resin, improve the hardness and wear resistance of the coating, and also helps to maintain the transparency and gloss of the coating.
[0010] S4, weigh 150-200 g of methylphenyl silicone resin and place it in a 500 mL beaker, and slowly add the modified graphene-silver nanoparticle composite obtained in step S2. Under stirring, add 15-20 g of hydrogenated silicone oil and the auxiliary agent solution obtained in step S3, and continue stirring until completely mixed. Add 2 g of ultraviolet absorber UV-531 to the above mixture, continue to stir evenly, and obtain a coating. In this step, the modified graphene-silver nanoparticle composite, hydrogenated silicone oil, auxiliary agent solution and ultraviolet absorber are mixed evenly to prepare a coating with excellent comprehensive performance. The addition of anti-ultraviolet improves the anti-ultraviolet and chemical corrosion resistance of the coating and extends the service life of the coating.
[0011] S5, cleaning, degreasing and drying the silicon steel substrate. The coating obtained in step S4 is evenly coated on the silicon steel substrate by spraying to form a coating with a thickness of 1-1.2 mm. The coated silicon steel sheet is placed in an oven and cured at 250-260 ° C for 10-20 min to completely cure the coating and obtain silicon steel containing the coating. The high temperature curing treatment in this step completely cures the coating, improves the hardness and adhesion of the coating, and ensures the long-term stability and durability of the coating.
[0012] Preferably, in step S1 of the present invention, 5 g of graphene is weighed and dispersed in 80 mL of ethanol, and ultrasonicated at a frequency of 40 kHz for 20 min using an ultrasonic disperser.
[0013] Preferably, in step S1 of the present invention, 3 g of polyethylene glycol diglycidyl ether (PEGDGE) is weighed, slowly added into the graphene dispersion while stirring, and ultrasonic treatment is continued for 50 min.
[0014] Preferably: in step S2 of the present invention, the graphene powder obtained in step S1 is redispersed in 50 mL of ethanol, and slowly added into 30 mL of ethanol solution containing 2 g of silver nitrate, while stirring, and the speed of the magnetic stirrer is set to 500 rpm.
[0015] Preferably: in step S2 of the present invention, 0.1 g of sodium borohydride is weighed and quickly added to the mixed solution, and the speed of the magnetic stirrer is immediately increased to 800 rpm.
[0016] Preferably: in step S3 of the present invention, 10 g of vinyltriethoxysilane is dissolved in 60 mL of acetone, which is marked as solution A, and 2 g of stannous octoate is dissolved in 20 mL of acetone, which is marked as solution B.
[0017] Preferably, in step S3 of the present invention, the microwave power is set to 600 W, the ultrasonic frequency is set to 20 kHz, and the reaction time is set to 45 min.
[0018] Preferably: in step S4 of the present invention, 200 g of methylphenyl silicone resin is weighed and placed in a 500 mL beaker.
[0019] Preferably: in step S5 of the present invention, the coated silicon steel sheet is placed in an oven and cured at 250° C. for 10 min.
[0020] Due to the adoption of the above technical solution, the technical progress achieved by the present invention is:
[0021] 1. The present invention modifies graphene by PEGDGE, thereby improving the dispersibility and stability of graphene and giving it additional functional expansion capabilities.
[0022] 2. The present invention combines silver nanoparticles with modified graphene to prepare a composite material with excellent electrical conductivity and antibacterial properties.
[0023] 3. The present invention utilizes microwave ultrasonic technology to rapidly prepare a uniform and transparent additive solution, which promotes the cross-linking reaction of the silicone resin, improves the hardness and wear resistance of the coating, and also helps to maintain the transparency and glossiness of the coating.
[0024] 4. In the process of coating preparation, the present invention achieves improvement in the comprehensive performance of the coating by adding a variety of functional components.
[0025] 5. The present invention introduces anti-ultraviolet and chemical corrosion resistant additives to improve the durability and service life of the coating.
[0026] 6. The present invention uses a spraying method to achieve uniform coating of the coating, and ensures complete curing and long-term stability of the coating through high-temperature curing treatment.
[0027] 7. The present invention achieves improved performance of the coating in terms of conductivity, antibacterial property, UV resistance, chemical corrosion resistance, hardness, wear resistance, etc. through the synergistic effect of modified graphene, silver nanoparticles, auxiliary solution and additives.
[0028] 8. The entire preparation process of the present invention focuses on process optimization and detail control to ensure the uniformity, stability and high performance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1-3 Scanning images of modified graphene prepared in Example 1 of the present invention and Comparative Examples 1-2.
[0030] Figure 4 The carbon steel coatings prepared in Example 2 of the present invention and Comparative Examples 3-4 were tested in three aspects: conductivity, electromagnetic shielding effectiveness and antibacterial performance.
[0031] Figure 5 The hardness, wear resistance loss and glossiness of the carbon steel coatings prepared for Example 3 of the present invention and Comparative Examples 5-7.
[0032] Figure 6 The initial decomposition temperature and the maximum decomposition rate temperature of the carbon steel coating prepared in Example 4 of the present invention and Comparative Examples 8-9. DETAILED DESCRIPTION
[0033] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict.
[0034] Example 1
[0035] S1. Weigh 5 g of graphene and disperse it in 80 mL of ethanol. Use an ultrasonic disperser to sonicate at a frequency of 40 kHz for 20 minutes to form a uniform graphene dispersion. Weigh 3 g of polyethylene glycol diglycidyl ether (PEGDGE) and slowly add it to the graphene dispersion while stirring and continue sonicating for 50 minutes to obtain a modified graphene dispersion. Use a centrifuge to centrifuge at 2000 r / min for 3 minutes to remove excess solvent and unadsorbed modifiers, and then vacuum dry at 60 °C for 18 hours to obtain modified graphene powder. The PEGDGE added in this step fixes PEGDGE on the graphene surface through surface adsorption and chemical bonding, and uses the steric hindrance effect of PEGDGE to improve the dispersibility and stability of graphene. The introduction of PEGDGE provides graphene with additional functional expansion capabilities.
[0036] S2. Redisperse the graphene powder obtained in step S1 in 50 mL of ethanol, and slowly add it to 30 mL of ethanol solution containing 2 g of silver nitrate, stirring while adding, and set the speed of the magnetic stirrer to 500 rpm to ensure uniform mixing. Weigh 0.1 g of sodium borohydride, quickly add it to the mixed solution, and immediately increase the speed of the magnetic stirrer to 800 rpm to ensure that the reducing agent is quickly dispersed and promote the reduction reaction. Continue stirring for 2 h to allow the reduction reaction to proceed fully. After the reaction is completed, the mixed solution is ultrasonically treated for 25 min to further break up the agglomerates that may be formed and improve the uniformity and dispersibility of the modified graphene-silver nanoparticle composite. The ultrasonically treated mixed solution is centrifuged at a speed of 2000 r / min for 3 min to remove unreacted silver nitrate, reducing agent and ethanol solvent. After centrifugation, the precipitate is washed 3 times with anhydrous ethanol to completely remove impurities. Finally, the washed precipitate was placed in a vacuum drying oven and dried at 50°C to constant weight to obtain a pure modified graphene-silver nanoparticle composite. The introduction of silver nanoparticles in this step significantly improved the conductivity of the composite material, which is helpful for the application of the coating in electromagnetic shielding, antistatic and other aspects. In addition, silver nanoparticles have excellent antibacterial properties and can give the coating antibacterial function.
[0037] S3. Dissolve 10 g of vinyl triethoxysilane in 60 mL of acetone, marked as solution A, and dissolve 2 g of stannous octoate in 20 mL of acetone, marked as solution B. Then mix the two solutions and place them in a microwave ultrasonic device. Set the microwave power to 600 W, the ultrasonic frequency to 20 kHz, and the reaction time to 45 min to obtain a uniform and transparent additive solution. The additive solution synthesized in this step helps to promote the cross-linking reaction of the silicone resin, improve the hardness and wear resistance of the coating, and also helps to maintain the transparency and gloss of the coating.
[0038] S4, weigh 150 g of methylphenyl silicone resin and place it in a 500 mL beaker, and slowly add the modified graphene-silver nanoparticle composite obtained in step S2. Under stirring, add 15 g of hydrogenated silicone oil and the auxiliary agent solution obtained in step S3, and continue stirring until completely mixed. Add 2 g of ultraviolet absorber UV-531 to the above mixture, continue to stir evenly, and obtain a coating. In this step, the modified graphene-silver nanoparticle composite, hydrogenated silicone oil, auxiliary agent solution and ultraviolet absorber are mixed evenly to prepare a coating with excellent comprehensive performance. The addition of anti-ultraviolet improves the anti-ultraviolet and chemical corrosion resistance of the coating and extends the service life of the coating.
[0039] S5, cleaning, degreasing and drying the silicon steel substrate. The coating obtained in step S4 is evenly coated on the silicon steel substrate by spraying to form a coating with a thickness of 1-1.2 mm. The coated silicon steel sheet is placed in an oven and cured at 250 ° C for 10 min to completely cure the coating and obtain silicon steel containing the coating. The high temperature curing treatment in this step completely cures the coating, improves the hardness and adhesion of the coating, and ensures the long-term stability and durability of the coating.
[0040] Comparative Example 1: Except that PEGDGE is not used to modify graphene in step S1, and graphene is directly dispersed in ethanol, the remaining steps are the same as those in Example 1.
[0041] Comparative Example 2: Except that sodium dodecylbenzene sulfonate (SDBS) is used instead of PEGDGE to modify graphene in step S1, the remaining steps are the same as those in Example 1.
[0042] Figure 1-3 The following are scanned images of the modified graphene prepared in Example 1 and Comparative Examples 1-2 of the present invention. Figure 1 It can be seen that the graphene layered structure is uniform and clear, each layer is arranged in a honeycomb shape, and the surface is covered with evenly distributed small holes, which are interconnected to form a three-dimensional grid pattern; Figure 2 The graphene in Example 2 has obvious agglomeration phenomenon, and the particles are large and unevenly distributed. This is because the long chain structure of PEGDGE can provide a steric hindrance effect, which effectively prevents the restacking and agglomeration of graphene sheets. In Comparative Example 2, there is a lack of PEGDGE modification, so agglomeration occurs; Figure 3 The graphene in the coating also showed a slight agglomeration phenomenon. It is speculated that the molecular structure of sodium dodecylbenzene sulfonate cannot provide sufficient steric hindrance, which makes the graphene more likely to agglomerate in subsequent treatment. This difference in microstructure directly leads to differences in the performance of the coating in terms of conductivity, stability, wear resistance, etc.
[0043] Example 2
[0044] S1. Weigh 6 g of graphene and disperse it in 100 mL of ethanol. Use an ultrasonic disperser to sonicate at a frequency of 40 kHz for 30 minutes to form a uniform graphene dispersion. Weigh another 5 g of polyethylene glycol diglycidyl ether (PEGDGE), slowly add it to the graphene dispersion while stirring, and continue sonication for 60 minutes to obtain a modified graphene dispersion. Use a centrifuge to centrifuge at 3000 r / min for 5 minutes to remove excess solvent and unadsorbed modifiers, and then vacuum dry at 80 °C for 24 hours to obtain modified graphene powder. The PEGDGE added in this step fixes PEGDGE on the graphene surface through surface adsorption and chemical bonding, and uses the steric hindrance effect of PEGDGE to improve the dispersibility and stability of graphene. The introduction of PEGDGE provides graphene with additional functional expansion capabilities.
[0045] S2. Redisperse the graphene powder obtained in step S1 in 60 mL of ethanol, and slowly add it to 40 mL of ethanol solution containing 3 g of silver nitrate, stirring while adding, and set the speed of the magnetic stirrer to 600 rpm to ensure uniform mixing. Weigh 0.2 g of sodium borohydride, quickly add it to the mixed solution, and immediately increase the speed of the magnetic stirrer to 900 rpm to ensure that the reducing agent is quickly dispersed and promote the reduction reaction. Continue stirring for 2.5 h to allow the reduction reaction to proceed fully. After the reaction is completed, the mixed solution is ultrasonically treated for 30 min to further break up the agglomerates that may be formed and improve the uniformity and dispersibility of the modified graphene-silver nanoparticle composite. The ultrasonically treated mixed solution is centrifuged at a speed of 3000 r / min for 5 min to remove unreacted silver nitrate, reducing agent and ethanol solvent. After centrifugation, the precipitate is washed 5 times with anhydrous ethanol to completely remove impurities. Finally, the washed precipitate was placed in a vacuum drying oven and dried at 60°C to constant weight to obtain a pure modified graphene-silver nanoparticle composite. The introduction of silver nanoparticles in this step significantly improves the conductivity of the composite material, which is helpful for the application of the coating in electromagnetic shielding, antistatic and other aspects. In addition, silver nanoparticles have excellent antibacterial properties and can give the coating antibacterial function.
[0046] S3, dissolve 12 g of vinyl triethoxysilane in 70 mL of acetone, marked as solution A, and dissolve 4 g of stannous octoate in 30 mL of acetone, marked as solution B. Then mix the two solutions and place them in a microwave ultrasonic device. Set the microwave power to 800 W, the ultrasonic frequency to 20 kHz, and the reaction time to 60 min to obtain a uniform and transparent additive solution. The additive solution synthesized in this step helps to promote the cross-linking reaction of the silicone resin, improve the hardness and wear resistance of the coating, and also helps to maintain the transparency and gloss of the coating.
[0047] S4, weigh 200 g of methylphenyl silicone resin and place it in a 500 mL beaker, and slowly add the modified graphene-silver nanoparticle composite obtained in step S2. Under stirring, add 20 g of hydrogenated silicone oil and the auxiliary agent solution obtained in step S3, and continue stirring until completely mixed. Add 2 g of ultraviolet absorber UV-531 to the above mixture, continue to stir evenly, and obtain a coating. In this step, the modified graphene-silver nanoparticle composite, hydrogenated silicone oil, auxiliary agent solution and ultraviolet absorber are mixed evenly to prepare a coating with excellent comprehensive performance. The addition of anti-ultraviolet improves the anti-ultraviolet and chemical corrosion resistance of the coating and extends the service life of the coating.
[0048] S5, the silicon steel substrate is cleaned, degreased and dried. The coating obtained in step S4 is evenly coated on the silicon steel substrate by spraying to form a coating with a thickness of 1.2 mm. The coated silicon steel sheet is placed in an oven and cured at 260 ° C for 20 min to completely cure the coating and obtain silicon steel containing the coating. The high temperature curing treatment in this step completely cures the coating, improves the hardness and adhesion of the coating, and ensures the long-term stability and durability of the coating.
[0049] Comparative Example 3: Except that the addition of silver nitrate and sodium borohydride is omitted in step S2, and silver nanoparticles are not introduced, the remaining steps are the same as those in Example 2.
[0050] Comparative Example 4: Except that the amount of silver nitrate in step S2 is reduced to 1 g, the remaining steps are the same as those in Example 2.
[0051] Samples of 1 cm×1 cm were cut from the silicon steel coatings prepared in Example 2 and Comparative Examples 3-4.
[0052] Conductivity test: Use a four-probe resistivity tester to apply uniform pressure on the coating surface, ensure that the probes are in good contact with the coating, and read and record the resistivity value displayed by the tester.
[0053] 2. Electromagnetic shielding effectiveness test: Place the coating sample to be tested in the test fixture, use a vector network analyzer to measure the SE value of the coating in the frequency range of 30 MHz to 1 GHz, and record and analyze the test results.
[0054] 3. Antibacterial performance test: prepare a certain amount of E. coli suspension, place the coating sample to be tested on the agar medium containing the E. coli suspension, culture at 37 ℃ for 24 h, take the culture medium for colony count, and calculate the antibacterial rate.
[0055] Table 1
[0056]
[0057] Table 1 and Figure 4 The carbon steel coating prepared for Example 2 of the present invention and Comparative Examples 3-4 was tested in three aspects: conductivity, electromagnetic shielding effectiveness and antibacterial performance. It can be seen from the table and the figure that Example 2 has excellent conductivity, electromagnetic shielding and antibacterial properties. In Comparative Example 3, the step of adding silver nitrate and sodium borohydride was omitted, that is, silver nanoparticles were not introduced. Silver nanoparticles play a key role in significantly improving conductivity, enhancing electromagnetic shielding performance and imparting antibacterial function in the composite material. Therefore, the composite material in Comparative Example 3 will have a significant decrease in conductivity, electromagnetic shielding and antibacterial performance compared to Example 2. In Comparative Example 4, the amount of silver nitrate is reduced to 1 g, resulting in a decrease in the number of silver nanoparticles generated and the distribution may be uneven, which will affect the overall effect of the silver nanoparticles in the composite material, including the reduction of conductivity, electromagnetic shielding performance and antibacterial performance. Although a certain amount of silver nanoparticles are still present, the effect will be significantly weakened compared to Example 2.
[0058] Example 3
[0059] S1. Weigh 5-6 g of graphene and disperse it in 85 mL of ethanol. Use an ultrasonic disperser to sonicate at a frequency of 40 kHz for 23 min to form a uniform graphene dispersion. Weigh 3.2 g of polyethylene glycol diglycidyl ether (PEGDGE) and slowly add it to the graphene dispersion while stirring and continue sonication for 53 min to obtain a modified graphene dispersion. Use a centrifuge to centrifuge at 2200 r / min for 4 min to remove excess solvent and unadsorbed modifier, and then vacuum dry at 65 °C for 20 h to obtain modified graphene powder. The PEGDGE added in this step fixes PEGDGE on the graphene surface through surface adsorption and chemical bonding, and uses the steric hindrance effect of PEGDGE to improve the dispersibility and stability of graphene. The introduction of PEGDGE provides graphene with additional functional expansion capabilities.
[0060] S2. Redisperse the graphene powder obtained in step S1 in 52 mL of ethanol, and slowly add it to 33 mL of ethanol solution containing 2.2 g of silver nitrate, stirring while adding, and set the speed of the magnetic stirrer to 530 rpm to ensure uniform mixing. Weigh 0.12 g of sodium borohydride, quickly add it to the mixed solution, and immediately increase the speed of the magnetic stirrer to 820 rpm to ensure that the reducing agent is quickly dispersed and promote the reduction reaction. Continue stirring for 2.2 h to allow the reduction reaction to proceed fully. After the reaction is completed, the mixed solution is ultrasonically treated for 27 min to further break up the agglomerates that may be formed and improve the uniformity and dispersibility of the modified graphene-silver nanoparticle composite. The ultrasonically treated mixed solution is centrifuged at a speed of 2200 r / min for 4 min to remove unreacted silver nitrate, reducing agent and ethanol solvent. After centrifugation, the precipitate is washed 4 times with anhydrous ethanol to completely remove impurities. Finally, the washed precipitate was placed in a vacuum drying oven and dried to constant weight at 52 °C to obtain a pure modified graphene-silver nanoparticle composite. The introduction of silver nanoparticles in this step significantly improved the conductivity of the composite material, which is helpful for the application of the coating in electromagnetic shielding, antistatic and other aspects. In addition, silver nanoparticles have excellent antibacterial properties and can give the coating antibacterial function.
[0061] S3, dissolve 11 g of vinyl triethoxysilane in 62 mL of acetone, marked as solution A, and dissolve 3 g of stannous octoate in 22 mL of acetone, marked as solution B. Then mix the two solutions and place them in a microwave ultrasonic device. Set the microwave power to 650 W, the ultrasonic frequency to 20 kHz, and the reaction time to 50 min to obtain a uniform and transparent additive solution. The additive solution synthesized in this step helps to promote the cross-linking reaction of the silicone resin, improve the hardness and wear resistance of the coating, and also helps to maintain the transparency and gloss of the coating.
[0062] S4, weigh 170 g of methylphenyl silicone resin and place it in a 500 mL beaker, and slowly add the modified graphene-silver nanoparticle composite obtained in step S2. Under stirring, add 17 g of hydrogen-containing silicone oil and the auxiliary agent solution obtained in step S3, and continue stirring until completely mixed. Add 2 g of ultraviolet absorber UV-531 to the above mixture, continue to stir evenly, and obtain a coating. In this step, the modified graphene-silver nanoparticle composite, hydrogen-containing silicone oil, auxiliary agent solution and ultraviolet absorber are mixed evenly to prepare a coating with excellent comprehensive performance. The addition of anti-ultraviolet improves the anti-ultraviolet and chemical corrosion resistance of the coating and extends the service life of the coating.
[0063] S5, the silicon steel substrate is cleaned, degreased and dried. The coating obtained in step S4 is evenly coated on the silicon steel substrate by spraying to form a coating with a thickness of 1.1 mm. The coated silicon steel sheet is placed in an oven and cured at 253 ° C for 13 min to completely cure the coating and obtain silicon steel containing the coating. The high temperature curing treatment in this step completely cures the coating, improves the hardness and adhesion of the coating, and ensures the long-term stability and durability of the coating.
[0064] Comparative Example 5: Except for omitting step S3 and not adding the auxiliary agent solution, the remaining steps are the same as those of Example 3.
[0065] Comparative Example 6: Except that the amount of the additive solution added in step S4 is reduced to 80% of the prepared amount, the remaining steps are the same as those in Example 3.
[0066] Comparative Example 7: Except that the amount of stannous octoate added in step S3 is adjusted to 1 g, the remaining steps are the same as those in Example 3.
[0067] Samples of 1 cm×1 cm were cut from the silicon steel coatings prepared in Example 3 and Comparative Examples 5-7, and hardness, wear resistance and glossiness were tested.
[0068] Hardness test: Use a pencil hardness tester to scratch the coating from low hardness to high hardness, and record the pencil hardness at which the scratch first appears.
[0069] Wear resistance test: Place the sample on a Taber wear tester, set the rotation speed to 5000 r, perform a wear test, and record the mass change before and after wear.
[0070] Gloss test: Use a gloss meter to measure the gloss of the coating at an angle of 60° and record the data.
[0071] Table 2
[0072]
[0073] Table 2 and Figure 5The hardness, wear resistance loss and glossiness test of carbon steel coating prepared for Example 3 of the present invention and Comparative Examples 5-7 are shown in the table and figure. The hardness value, wear resistance loss and glossiness value of Example 3 are better than those of Comparative Examples 5-7. Comparative Example 5 omits step S3, i.e., no auxiliary solution is added. Comparative Example 7 reduces the amount of auxiliary solution added. The auxiliary solution plays an important role in promoting cross-linking reaction, improving the hardness and wear resistance of the coating, and maintaining transparency and glossiness in the coating. Not adding or adding less will lead to insufficient cross-linking degree of the coating, thereby affecting its hardness, wear resistance and overall performance. Therefore, compared with Example 3, the comprehensive performance of the coating prepared by Comparative Examples 5-6 is reduced. Comparative Example 7 adjusts the amount of stannous octoate added and reduces its dosage. Stannous octoate is a key component in the auxiliary solution and has an important influence on the cross-linking reaction. Reducing its dosage may lead to insufficient cross-linking reaction, thereby affecting the hardness and wear resistance of the coating.
[0074] Example 4
[0075] S1. Weigh 5.6 g of graphene and disperse it in 90 mL of ethanol. Use an ultrasonic disperser to sonicate at a frequency of 40 kHz for 26 min to form a uniform graphene dispersion. Weigh another 5 g of polyethylene glycol diglycidyl ether (PEGDGE), slowly add it to the graphene dispersion while stirring, and continue sonication for 56 min to obtain a modified graphene dispersion. Use a centrifuge to centrifuge at 2800 r / min for 4 min to remove excess solvent and unadsorbed modifier, and then vacuum dry at 75 °C for 22 h to obtain modified graphene powder. The PEGDGE added in this step fixes PEGDGE on the graphene surface through surface adsorption and chemical bonding, and uses the steric hindrance effect of PEGDGE to improve the dispersibility and stability of graphene. The introduction of PEGDGE provides graphene with additional functional expansion capabilities.
[0076] S2. Redisperse the graphene powder obtained in step S1 in 58 mL of ethanol, and slowly add it to 32 mL of ethanol solution containing 2.8 g of silver nitrate, stirring while adding, and set the speed of the magnetic stirrer to 550 rpm to ensure uniform mixing. Weigh 0.18 g of sodium borohydride, quickly add it to the mixed solution, and immediately increase the speed of the magnetic stirrer to 880 rpm to ensure that the reducing agent is quickly dispersed and promote the reduction reaction. Continue stirring for 2.3 h to allow the reduction reaction to proceed fully. After the reaction is completed, the mixed solution is ultrasonically treated for 28 min to further break up the agglomerates that may be formed and improve the uniformity and dispersibility of the modified graphene-silver nanoparticle composite. The ultrasonically treated mixed solution is centrifuged at a speed of 2800 r / min for 5 min to remove unreacted silver nitrate, reducing agent and ethanol solvent. After centrifugation, the precipitate is washed 3 times with anhydrous ethanol to completely remove impurities. Finally, the washed precipitate was placed in a vacuum drying oven and dried at 58 °C to constant weight to obtain a pure modified graphene-silver nanoparticle composite. The introduction of silver nanoparticles in this step significantly improved the conductivity of the composite material, which is helpful for the application of the coating in electromagnetic shielding, antistatic and other aspects. In addition, silver nanoparticles have excellent antibacterial properties and can give the coating antibacterial function.
[0077] S3, dissolve 12 g of vinyl triethoxysilane in 68 mL of acetone, marked as solution A, and dissolve 3 g of stannous octoate in 25 mL of acetone, marked as solution B. Then mix the two solutions and place them in a microwave ultrasonic device. Set the microwave power to 750 W, the ultrasonic frequency to 20 kHz, and the reaction time to 55 min to obtain a uniform and transparent additive solution. The additive solution synthesized in this step helps to promote the cross-linking reaction of the silicone resin, improve the hardness and wear resistance of the coating, and also helps to maintain the transparency and gloss of the coating.
[0078] S4, weigh 180 g of methylphenyl silicone resin and place it in a 500 mL beaker, and slowly add the modified graphene-silver nanoparticle composite obtained in step S2. Under stirring, add 19 g of hydrogen-containing silicone oil and the auxiliary agent solution obtained in step S3, and continue stirring until completely mixed. Add 2 g of ultraviolet absorber UV-531 to the above mixture, continue to stir evenly, and obtain a coating. In this step, the modified graphene-silver nanoparticle composite, hydrogen-containing silicone oil, auxiliary agent solution and ultraviolet absorber are mixed evenly to prepare a coating with excellent comprehensive performance. The addition of anti-ultraviolet improves the anti-ultraviolet and chemical corrosion resistance of the coating and extends the service life of the coating.
[0079] S5, the silicon steel substrate is cleaned, degreased and dried. The coating obtained in step S4 is evenly coated on the silicon steel substrate by spraying to form a coating with a thickness of 1.2 mm. The coated silicon steel sheet is placed in an oven and cured at 260 ° C for 12 min to completely cure the coating and obtain silicon steel containing the coating. The high temperature curing treatment in this step completely cures the coating, improves the hardness and adhesion of the coating, and ensures the long-term stability and durability of the coating.
[0080] Comparative Example 8: Except for using polyurethane resin instead of methylphenyl silicone resin in step S4, the remaining steps are the same as those in Example 4.
[0081] Comparative Example 9: Except that ethyl silicone resin is used instead of methylphenyl silicone resin in step S4, the remaining steps are the same as those of Example 4.
[0082] Thermogravimetric analysis (TGA) method: Cut samples of 1 cm×1 cm from the silicon steel coatings prepared in Example 4 and Comparative Examples 8-9, respectively, put the samples into a thermogravimetric analyzer, introduce nitrogen as a protective gas, set the heating rate to 10°C / min, and increase the temperature from room temperature to 800°C. Record and analyze the thermogravimetric curve to determine the initial decomposition temperature and the maximum decomposition rate temperature.
[0083] Table 3
[0084]
[0085] Table 3 and Figure 6 The initial decomposition temperature and the maximum decomposition rate temperature of the carbon steel coating prepared for Example 4 and Comparative Examples 8-9 of the present invention can be seen from the table and the figure that the high temperature resistance of Example 4 is better than that of Comparative Examples 8-9. Compared with Example 4, Comparative Examples 8 and 9 use polyurethane resin and ethyl silicone resin in the coating formula instead of methyl phenyl silicone resin, respectively. Although polyurethane resin has excellent physical and mechanical properties and chemical corrosion resistance, its high temperature resistance is generally not as good as methyl phenyl silicone resin. In a high temperature environment, polyurethane resin may be more prone to thermal decomposition or degradation, resulting in a decrease in coating performance. Although ethyl silicone resin is also a type of silicone resin, its molecular structure and properties may be different from those of methyl phenyl silicone resin. The stability of ethyl silicone resin at high temperatures may not be as good as that of methyl phenyl silicone resin, especially in a complex system containing modified graphene-silver nanoparticle composites, its high temperature resistance will be more affected.
[0086] The above-mentioned embodiments only express the specific implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present invention. It should be pointed out that, for those skilled in the art, without departing from the concept of the present invention, any other changes, modifications, substitutions, combinations, simplifications made without departing from the spirit and principle of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a thick coating suitable for the surface of silicon steel, characterized in that: The specific preparation method is as follows: S1. Weigh 5-6 g of graphene and disperse it in 80-100 mL of ethanol. Use an ultrasonic disperser to ultrasonicate at a frequency of 40 kHz for 20-30 min to form a graphene dispersion. Weigh 3-5 g of polyethylene glycol diglycidyl ether PEGDGE and slowly add it to the graphene dispersion while stirring. Continue ultrasonication for 50-60 min to obtain a modified graphene dispersion. Use a centrifuge to centrifuge at 2000-3000 r / min for 3-5 min, and then vacuum dry at 60-80 ° C for 18-24 h to obtain a modified graphene powder. S2, re-dispersing the graphene powder obtained in step S1 in 50-60 mL of ethanol, and slowly adding it to 30-40 mL of ethanol solution containing 2-3 g of silver nitrate, stirring while adding, and setting the speed of the magnetic stirrer to 500-600 rpm; weighing 0.1-0.2 g of sodium borohydride, quickly adding it to the mixed solution, and immediately increasing the speed of the magnetic stirrer to 800-900 rpm, and continuing to stir for 2-2.5 h. After the reaction is completed, the mixed solution is subjected to ultrasonic treatment for 25-30 min; the mixed solution after ultrasonic treatment is centrifuged, and the speed is set to 2000-3000 r / min for 3-5 min. After centrifugation, the precipitate is washed 3-5 times with anhydrous ethanol. Finally, the washed precipitate is placed in a vacuum drying oven and dried to constant weight at 50-60 ° C to obtain a pure modified graphene-silver nanoparticle composite; S3, dissolving 10-12 g of vinyl triethoxysilane in 60-70 mL of acetone, marked as solution A, dissolving 2-4 g of stannous octoate in 20-30 mL of acetone, marked as solution B; then mixing the two solutions and placing them in a microwave ultrasonic device; setting the microwave power to 600-800 W, the ultrasonic frequency to 20 kHz, and the reaction time to 45-60 min to obtain a uniform and transparent additive solution; S4, weigh 150-200 g of methylphenyl silicone resin and place it in a 500 mL beaker, slowly add the modified graphene-silver nanoparticle composite obtained in step S2; under stirring, add 15-20 g of hydrogenated silicone oil and the auxiliary agent solution obtained in step S3, and continue to stir until completely mixed; add 2 g of ultraviolet absorber UV-531 to the above mixture, continue to stir evenly, and obtain a coating; S5. Clean, degrease and dry the silicon steel substrate; evenly coat the coating obtained in step S4 on the silicon steel substrate by spraying to form a coating with a thickness of 1-1.2 mm; place the coated silicon steel sheet in an oven and perform a curing treatment at 250-260 °C for 10-20 min to completely cure the coating to obtain silicon steel containing the coating.
2. The method for preparing a thick coating suitable for the surface of silicon steel according to claim 1, characterized in that: In the step S1, 5 g of graphene was weighed and dispersed in 80 mL of ethanol, and ultrasonicated at a frequency of 40 kHz for 20 min using an ultrasonic disperser.
3. A method for preparing a thick coating suitable for the surface of silicon steel according to claim 1 or 2, characterized in that: In the step S1, 3 g of polyethylene glycol diglycidyl ether PEGDGE was weighed, slowly added into the graphene dispersion while stirring, and ultrasonic treatment was continued for 50 min.
4. The method for preparing a thick coating suitable for the surface of silicon steel according to claim 3, characterized in that: In the step S2, the graphene powder obtained in the step S1 is redispersed in 50 mL of ethanol, and slowly added into 30 mL of ethanol solution containing 2 g of silver nitrate, while stirring, and the speed of the magnetic stirrer is set to 500 rpm.
5. The method for preparing a thick coating suitable for the surface of silicon steel according to claim 4, characterized in that: In step S2, 0.1 g of sodium borohydride was weighed and quickly added to the mixed solution, and the speed of the magnetic stirrer was immediately increased to 800 rpm.
6. A method for preparing a thick coating suitable for the surface of silicon steel according to claim 1 or 5, characterized in that: In the step S3, 10 g of vinyltriethoxysilane is dissolved in 60 mL of acetone, which is marked as solution A, and 2 g of stannous octoate is dissolved in 20 mL of acetone, which is marked as solution B.
7. The method for preparing a thick coating suitable for the surface of silicon steel according to claim 1, characterized in that: In step S3, the microwave power is set to 600 W, the ultrasonic frequency is set to 20 kHz, and the reaction time is set to 45 min.
8. The method for preparing a thick coating suitable for the surface of silicon steel according to claim 1, characterized in that: In step S4, 200 g of methylphenyl silicone resin was weighed and placed in a 500 mL beaker.
9. The method for preparing a thick coating suitable for the surface of silicon steel according to claim 8, characterized in that: In step S5, the coated silicon steel sheet is placed in an oven and cured at 250° C. for 10 min.
10. A thick coating suitable for the surface of silicon steel obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of anticorrosive coating
CN106085139A
Preparing method of photochromic corrosion resistant paint
CN106189717A